2021
DOI: 10.1038/s41398-021-01357-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between latent trauma and brain structure in children

Abstract: The developing brain is marked by high plasticity, which can lead to vulnerability to early life stressors. Previous studies indicate that childhood maltreatment is associated with structural aberrations across a number of brain regions. However, prior work is limited by small sample sizes, heterogeneous age groups, the examination of one structure in isolation, the confounding of different types of early life stressors, and not accounting for socioeconomic status. These limitations may contribute to high vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…However, our study revealed that the FC between the left MFG and bilateral putamen had no observable discrepancy in the MDD with the childhood trauma group compared with the MDD without the childhood trauma group. Jeong et al (2021) found that trauma exposure may be related to structural alterations in the MFG and putamen. Thus, trauma exposure may also be an important factor underlying structural abnormalities of the MFG and putamen, but we need further research to find out if there are also functional abnormalities in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study revealed that the FC between the left MFG and bilateral putamen had no observable discrepancy in the MDD with the childhood trauma group compared with the MDD without the childhood trauma group. Jeong et al (2021) found that trauma exposure may be related to structural alterations in the MFG and putamen. Thus, trauma exposure may also be an important factor underlying structural abnormalities of the MFG and putamen, but we need further research to find out if there are also functional abnormalities in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, putamen volume and function changes have been shown in post-traumatic stress disorder (PTSD). Recent studies have shown a negative correlation between childhood trauma and putamen volume [ 56 , 57 ]. In addition, fMRI studies have reported increased putamen activation to unconditioned stimulus and decreased putamen-amygdala connectivity in PTSD subjects [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Adolescent Brain Cognitive Development (ABCD) study presents a unique resource to characterize the longitudinal impact of comorbid trauma and substance use in the developing brain [ 69 ]. The largest longitudinal study of neurodevelopment, ABCD characterizes trauma [ 70 ] and substance use [ 71 ]. While the study is designed to complete baseline assessments prior to the onset of regular substance use [ 69 ], one limitation may be the degree to which the occurrence of early childhood trauma prior to enrollment is fully captured.…”
Section: Summary and Future Directionsmentioning
confidence: 99%